Treatment of severe psoriasis with infliximab : report of two cases - Peternel, Sandra (Array, 2009)
Summary: Infliximab is an anti-tumor necrosis factor-α monoclonal antibody shown to be effective in the treatment of moderate-to-severe psoriasis and psoriatic arthritis. We report on the first two patients in Croatia in which the efficacy of infliximab therapy was monitored and evaluated primarily on the basis of cutaneous manifestations of psoriasis. Both patients had severe, treatment-resistant chronic plaque psoriasis and psoriatic arthritis and were on methotrexate therapy before the initiation and throughout the course of infliximab treatment. Infliximab was administered intravenously at a dose of 4 or 5 mg/kg at week 0, 2, 6 and every 8 weeks thereafter. Disease severity was measured before each infusion by means of Psoriasis Area and Severity Index (PASI) score. A remarkable clinical response was achieved in both patients with a 50% or greater improvement in baseline PASI at week 2 after therapy initiation and a 90% or greater improvement at week 6 in one patient and at week 14 in the other. Both patients also reported a significant decline in their arthritis symptoms shortly after the introduction of infliximab. The concomitant use of infliximab and methotrexate in these two patients resulted in rapid and sustained remission of psoriasis with no major adverse effects detected